Nail disease in psoriatic arthritis. Data from the Russian Psoriatic Arthritis Registry - E. E. Gubar; Y. L. Korsakova; E. Yu. Loginova; T. V. Korotaeva; E. A. Vasilenko; A. A. Vasilenko; N. A. Kuznetsova; I. M. Patkikeeva; E. L. Nasonov (Научно-практическая ревматология, 2021)
Objective of the study – to compare, in real clinical practice, according to the data of the Russian Psoriatic Arthritis Registry, characteristics of two groups of psoriatic arthritis (PsA) patients: with and without nail psoriasis.Material and methods. 588 PsA patients (277 males and 311 females) with PsA according to CASPAR criteria were included in the Russian Psoriatic Arthritis Registry. Patients’ age was 48.6±0.5 years, disease duration – 7.0±0.3 years. Patients underwent standard clinical examination of PsA activity. Disease activity measures evaluated in this study included DAPSA (Disease Activity in Psoriatic Arthritis), BASDAI (Bath Ankylosing Spondylitis Disease Activity Index) and ASDAS-СRP (Ankylosing Spondylitis Disease Activity Score). Enthesitis was measured using LEI (Leeds Enthesitis Index) index. Dactylitis was detected, the number of digits with acute dactylitis was defined. Skin lesion severity was evaluated in terms of BSA (Body Surface Area) affected, and PASI (Psoriasis Area Severity Index); PASI was calculated in case BSA > 3%. The criteria of minimal disease activity (MDA) had been used to assess the treatment efficiency. MDA was achieved if a patient met ≥5 of the 7 following categories: tender joint count (TJC) ≤1, swollen joint count (SJC) ≤1, PASI≤1 or BSA≤3%, patient pain VAS ≤15, patient global activity (PGA) VAS ≤20, Health Assessment Questionnaire Disability Index (HAQ) ≤0.5, and tender entheseal points ≤1. Patients were split into two groups: those with nail psoriasis (group 1), and those without nail psoriasis (group 2).Results. 312 (53.1%) patients had nail psoriasis and 276 (46.9%) did not. Patients’ age in group 1 was 45.7±11.9 years, in group 2 – 48.8±13.2 years (р>0.05). PsA duration in groups 1 and 2 did not differ, it was 7.1±6.6 and 7.0±6.2 years respectively (р>0.05). Higher proportions of patients with nail psoriasis were male, disabled from working and chronic smokers compared to patients without nail psoriasis: 51.9% vs 44.1% (р=0.013), 37.20% vs 26.40% (р<0.01) and 18.9% vs 8.7% (р<0.01) respectively. Patients with nail psoriasis had more severe erosive peripheral arthritis compared to patients without nail psoriasis. Median TJC was 8 [4–15] vs 5 [2–12] (р=0.002), SJC – 5 [1–9] vs 2 [0–7] (р=0.003), and erosive radiographic arthritis of feet was found in 45.0% vs 31.2% of patients (р=0.003) respectively. Group 1 patients had higher disease activity measured by DAPSA – 25 [15–39] vs 20 [12–33] (p=0.001) and ASDAS-CRP – 3.1 [2.2–4.0] vs 2.8 [1.8–3.5] (р=0.004), compared to group 2 patients. Patients with nail psoriasis had higher frequency of heel enthesitis and dactylitis; axial disease was diagnosed more often among them, compared to patients without nail psoriasis. Heel enthesitis was detected in 53 (17.0%) vs 28 (10.1%; р=0.016), dactylitis – in 76 (24.4%) vs 46 (16.7%; р=0.022), spondylitis – in 109 (35.0%) vs 73 (26.4%; р=0.025) patients respectively. Patients in group 1 had worse skin psoriasis than in group 2. Patients with nail psoriasis significantly more often had moderate and severe skin psoriasis according to BSA, compared to patients without nail psoriasis (39.9% vs 26.1% and 14.8 vs 1.1% respectively; р<0.01 for both comparisons); group 2 patients significantly more often had limited skin psoriasis compared to group 1 patients – in 72.8% vs 45.3% of cases respectively (р<0.01). Median PASI index in groups 1 and 2 was 6 [2–14] vs 3 [1–6] respectively (р<0.01). Group 1 patients gave worse assessment of their disease than group 2 patients; median PGA was 50 [40–70] mm vs 50 [30–65] mm VAS respectively (р=0.044). Less patients with nail psoriasis compared to patients without nail psoriasis had achieved MDA throughout the whole study. At the first visit MDA was detected in 3% vs 9% (р=0.006) of patients, at the second – in 12% vs 27% (р<0.001), at the third – in 14% vs 28% (р=0.011), at the fourth – in 17% vs 38% (р<0.001) and at the fifth in 27% vs 52% (р=0.004) of patients respectively. Patients with and without nail psoriasis were given equivalent therapy with diseasemodifying antirheumatic drugs (DMARDs) and biological agents (bDMARDs). DMARDs were given to 78.2% and 80.1% of patients respectively (р>0.05), it was mostly methotrexate (MTX); MTX was used in 66.0% and 64.1% of cases respectively (р>0.05). bDMARDs were prescribed to 22.1% and 28.3% (р>0.05) of patients, including tumour necrosis factor (TNF) inhibitors – in 67% and 63% of cases, interleukin (IL) inhibitors – in 33% and 37% of cases (р>0.05 for both comparisons). Taking into account the similar disease duration and equivalent therapy in both groups, it could be concluded that patients with nail psoriasis achieved MDA less frequently due to greater disease severity.Conclusion. Nail involvement is identified in more than half (53%) of PsA patients of the Russian Psoriatic Arthritis Registry. Nail psoriasis is associated with significantly worse disease status as measured by severe peripheral arthritis, enthesitis, dactylitis, spondylitis and skin lesions; higher frequency of erosive arthritis was detected in this category of patients. Patients with nail psoriasis had achieved MDA less frequently compared to patients without nail psoriasis. Nail involvement is associated with worse response to therapy and patients’ disability. These data emphasize the importance of accurate diagnostics of nail psoriasis and optimization of treatment approach, including “targeted” therapy.